Pathogenicity of Colletotrichum spp. Isolated from Shallot in Special Region of Yogyakarta and Central Java - Chomayaroh, Devinda Mardhalita; Wibowo, Arif; Suryanti, Suryanti (Universitas Gadjah Mada, 2025)
Anthracnose disease on shallots is an important diseases caused by Colletotrichum gleosporioides species complex. The purpose of the study was to determine the pathogenicity of 11 Colletotrichum spp. isolates, originating from several shallot production centers in Central Java and Special Region of Yogyakarta, as well as detect the ability of isolates to produce specific enzymes. The pathogenicity test was carried out by inoculating shallot varieties Tajuk, using a spore suspension. Inoculation was carried out by spraying 10 mL of spore suspension with a density of 104/mL to each plant and were then covered using clear plastic, for 24 hours. Enzyme production tested in vitro included cellulase, amylase, laccase and protease. Results showed that all isolates tested were pathogenic and the most infectious was the isolate UGM_CIM_P from Imogiri with disease incidence of 49%. All isolates were able to show cellulase activity, with the highest activity found in the UGM_CIM_P isolate. All isolates tested showed no amylase, laccase, and protease activities.